Factors influencing self-acceptance in cancer patients: A systematic review - Bergita Olivia Hali Samon; Allenidekania Allenidekania; Agung Waluyo; Dewi Gayatri (Malahayati International Journal of Nursing and Health Science, 2025)
Background: A cancer diagnosis often has a significant impact on patients’ psychological aspects, particularly on self-acceptance. Purpose: To identify and summarize various factors influencing self-acceptance in cancer patients. Method: The selection process followed the PRISMA guidelines. Literature searches were conducted in PubMed, Scopus, and Google Scholar databases for studies published between 2010 and 2025, including English-language articles with quantitative study designs (cross-sectional, cohort, case-control, or case report), involving cancer patients aged ≥18 years. Results: Nine studies met the criteria for further analysis. Factors influencing self-acceptance included sociodemographic factors (age, gender, education, income, residence, marital status, employment status, social support, educational level, economic status), disease-related factors (TNM stage, metastasis status, disease duration), and psychosocial factors (social support, meaning-making, fear of recurrence). Conclusion: Self-acceptance in cancer patients is influenced by sociodemographic, disease-related, and psychosocial factors. These findings are important for developing more targeted psychosocial interventions to improve the well-being of cancer patients.